2020
DOI: 10.1038/s41598-020-74997-8
|View full text |Cite
|
Sign up to set email alerts
|

Individual dietary specialization reduces intraspecific competition, rather than feeding activity, in black amur bream (Megalobrama terminalis)

Abstract: Individual specialization and high plasticity in feeding activity are common in natural populations. However, the role of these two in intraspecific competition is unclear. In this study, the rhythm of feeding activity, dietary composition, niche width, niche overlap, and individual specialization was explored in four different size groups of black amur bream (Megalobrama terminalis), using microscopic identification of foregut contents and stable isotope analysis (δ13C and δ15N) of dorsal muscle. Both methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 57 publications
(74 reference statements)
2
10
0
1
Order By: Relevance
“…Interactions among species and environmental conditions may vary over time, influencing both individual and population niches. Our study, brings novel insights to the understanding of individual and population niche variation of animals on a large time perspective through changes in competition levels, whereas the majority of studies primarily focus on short and seasonal dynamics (Bolnick et al 2010, Araújo et al 2011, Cloyed and Eason 2016, Costa‐Pereira et al 2019, Xia et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interactions among species and environmental conditions may vary over time, influencing both individual and population niches. Our study, brings novel insights to the understanding of individual and population niche variation of animals on a large time perspective through changes in competition levels, whereas the majority of studies primarily focus on short and seasonal dynamics (Bolnick et al 2010, Araújo et al 2011, Cloyed and Eason 2016, Costa‐Pereira et al 2019, Xia et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This response to a reversal of the intensity of intraspecific competition is in accordance with both theoretical considerations (Roughgarden 1972, Svanbäck and Bolnick 2005) and observational and experimental studies (Svanbäck and Bolnick 2007, Huss et al 2008, Araújo et al 2011), which have shown that high intraspecific competition promotes increased population niche width via individual specialization and greater between‐individual variation. The individual diet specialization towards different prey types increases the diversity and inter‐individual differences in prey utilization, thereby promoting resource partitioning among conspecific individuals, which may alleviate the effects of strong intraspecific competition (Xia et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overlap of SEA c and SEA B of grass carp between sampling regions was estimated and plotted. We also illustrated the stable isotope values of the potential prey by sampling and detecting or referencing relevant publications with the same study area, including (Zeng et al 2018a), (Zeng et al 2018b) and (Xia et al 2020). All data analyses were performed in R 4.0.3.…”
Section: Stable Isotope Detection and Data Analysismentioning
confidence: 99%
“…For instance, M. hoffmanni is an omnivorous fish that feeds mostly on benthic creatures such as freshwater shellfish, river clams, organic detritus, and some aquatic plants [ 9 ]. M. skolkovii and M. pellegrini are omnivorous as well, however, they primarily feed on aquatic plants [ 10 ]. Importantly, in M. pellegrini , the development of the upper and lower jaws as well as the thickening of the stratum corneum have strengthened the scraping function, making it more conducive to feeding on stationary organisms [ 6 ].…”
Section: Introductionmentioning
confidence: 99%